Intolerance of Uncertainty and Tendency to Worry as Mediators Between Trust in Institutions and Social Support and Fear of Coronavirus and Consequences of the Pandemic - Gvozden, Tatjana Vukosavljević; Baucal, Aleksandar; Krstic, Ksenija; Filipović, Severina (Frontiers in Psychology, 2021)
The aim of this paper is to formulate and test a model integrating cognitive behavioral theory (CBT) findings regarding the importance of intolerance of uncertainty and tendency to worry with findings regarding the importance of trust in institutions, other people, and social support. We assumed that trust in institutions, other people, and social support reduce fear of the coronavirus and of the consequences of the pandemic in a direct way, but also indirectly by enhancing one’s sense of control and diminishing the tendency to worry which, further, attenuates fear of the coronavirus and fear of the consequences of the pandemic. An online survey was conducted among the Serbian general population (N = 1409, 78.1% female, M = 38.82, SD = 9.24) at the end of April 2020, which included questionnaires on fear of SARS-CoV-2, fear of consequences of the pandemic, social support, trust in other people and trust in political and health institutions. The model has been validated by data from our study suggesting that it represents one possible pattern of interrelationships between social and intrapsychic variables in the pandemic situation. Results also showed that the COVID-19 related fears are related more strongly to intrapsychic variables - IU and tendency to worry - than to variables operationalizing social context relevant for coping with pandemic at the social and individual level.